An exploratory study on Musharakah SRI Sukuk for the development of Waqf properties/assets in Malaysia. (9th March 2020) - Zain, Nor Syahirah; Muhamad Sori, Zulkarnain
Abstract : Purpose: This study aims to explore a sustainable and responsible investment (SRI) sukuk model based on Musharakah that could be implemented to develop waqf properties and assets under the SRI sukuk framework in Malaysia. This includes proposing and designing a potential SRI sukuk model and seeking the opinion of subject-matter experts and industry practitioners on the model, its attractiveness to investors and its feasibility to implement in Malaysia. Design/methodology/approach: The study adopts desk research and semi-structured interview as its methodology. A desk research is where a detailed critical review and analysis of past literature from reports, journals, framework, books and practices are undertaken. To establish a SRI sukuk model, the paper also studies the cases of the first SRI sukuk issued in Malaysia and other waqf -related sukuks that have been structured for the development of waqf property/asset in the past. Following that, the opinion of subject-matter experts and industry practitioners on the proposed SRI sukuk model is sought in a semi-structured interview. Findings: Based on the interviewees' response, the study proposes the most feasible SRI sukuk model that could be implemented in the Malaysian context for the development of waqf properties/assets, which is a Musharakah -based sukuk model. The model will be elaborated based on the purpose of development, functionality, choice of Shari'ah contract, obligor and return mechanism. Research limitations/implications: This paper is exploratory in nature. While it explores the structural point of view only, future research could analyse and identify the legal, regulatory, financial and Shari'ah aspects of the proposed model. Further empirical studies can be done to provide more comprehensive idea and knowledge regarding the subject matter. Practical implications: The study serves great benefit to the government, waqf administrators, regulators, policymakers, foundations, corporations and interested investors to explore SRI sukuk as one of the feasible financial instruments to develop waqf in Malaysia. Originality/value: This study proposes the use of an innovative financial instrument called SRI sukuk and structures a feasible SRI sukuk model to help realise the true roles of waqf as not only a religious tool but also one of the instruments for human, economic and social developments.